2021
DOI: 10.1111/his.14369
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for progression of appendiceal neuroendocrine tumours: low‐stage tumours <5 mm appear to be overwhelmingly indolent and may merit a separate designation

Abstract: Aims Appendiceal well‐differentiated neuroendocrine tumours (NETs) are usually incidental and clinically benign. Several studies have reported different risk factors for nodal metastasis. The aim of this study was to investigate our appendiceal NETs (App‐NETs) to determine the factors associated with malignant behaviour. Methods and results For 120 App‐NETs, we reviewed the clinical presentation and follow‐up, including serum chromogranin A (CgA) levels, and compiled several microscopic variables. Pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Tubular NETs: These tumors represent < 10% of all aNETs[ 8 ] and must be distinguished from adenocarcinoma NOS and goblet cell adenocarcinoma[ 14 ].…”
Section: What Are the Features Analyzed In The Histopathological Diag...mentioning
confidence: 99%
See 4 more Smart Citations
“…Tubular NETs: These tumors represent < 10% of all aNETs[ 8 ] and must be distinguished from adenocarcinoma NOS and goblet cell adenocarcinoma[ 14 ].…”
Section: What Are the Features Analyzed In The Histopathological Diag...mentioning
confidence: 99%
“…After a CRH, residual disease or lymph node involvement is present in 0% to 40% of cases[ 2 , 8 , 28 ]. A recent review by Webb et al [ 11 ] of patients in the National Cancer Database treated with surgery found that, unlike other types of appendiceal neoplasms, in aNET, the presence of regional LNM does not reduce overall survival.…”
Section: Indications In the Literature For A Completion Right Colectomymentioning
confidence: 99%
See 3 more Smart Citations